(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: The world is facing COVID-19 pandemic and almost 70% of the world had gone under Lockdown. People are facing stress, insomnia and anxiety. The lack of basic awareness and spread of fake news are common causes of all these issues. This study was done to determine the prevalence of insomnia and anxiety in medical and non-medical students. Subjects and methods: Subjects were approached through friends in universities using WhatsApp. People having insomnia and anxiety before quarantine were excluded from this study. People using anti-depressants and anti-psychotics before quarantine were also excluded from this study. A descriptive cross-sectional study was conducted among 965 students of medical and non-medical universities in the cities of Lahore, Rawalpindi and Islamabad. Consent was taken for using the Hamilton Anxiety Rating Scale and Insomnia Severity Index for scoring of anxiety and insomnia respectively. An online questionnaire made in Google forms was used for data collection. Independent t-tests, Pearson Correlation and Regression analysis were performed using SPSS v25. Results: Increased prevalence of anxiety and insomnia in non-medical students as compared to the medical students was observed. There was statistically significant strong correlation between anxiety and insomnia of the enrolled subjects (r=0.742, p<0.001). A linear regression equation was formulated. Increased prevalence of anxiety and insomnia in females was also determined. Conclusion: Non-medical students, compared to medical students, among which, females, compared to males, were more likely to suffer from anxiety and insomnia during lockdown.